Electoral mechanisms and pressure groups: The mix of direct and indirect taxation - Gianluca Fiorentini (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper describes the fiscal structure of a community as an equilibrium of a non-cooperative game where members of different pressure groups - characterised by conflicting interests - compete to get distributive gains. Their interaction is regulated by a constitution which sets the electoral rules and the institutional framework in which pressure groups' activities take place. We focus on how the equilibrium mix of direct and indirect taxation is determined in a community divided into two groups working in different sectors which we label regular and shadow sectors, respectively. Our main aim is to investigate the relations between the relative scale of the shadow sector, the fiscal equilibrium between direct and indirect taxation, and the constitutional setting. In this respect we show that the constitutional settings in which the main legislative body is chosen through a strictly proportional electoral rule tend to determine a fiscal equilibrium with a greater emphasis on direct taxation and this in turn gives greater incentives to enlarge the shadow sector. The paper provides empirical evidence on 21 OECD countries for the period 1970-90 on the relevance of the features of the electoral mechanisms on the fiscal mix between direct and indirect taxation.
Keywords: 330; Interessenpolitik; Wahlsystem; Direkte Besteuerung; Indirekte Besteuerung; Schattenwirtschaft; Spieltheorie; Theorie